Impact of the timing and the nature of nitrogen additions on the production kinetics of fermentative aromas by Saccharomyces cerevisiae during winemaking fermentation in synthetic media. (December 2018) - Seguinot, Pauline; Rollero, Stéphanie; Sanchez, Isabelle; Sablayrolles, Jean-Marie; Ortiz-Julien, Anne; Camarasa, Carole; Mouret, Jean-Roch
Abstract: During alcoholic fermentation, many parameters, including the nitrogen composition of the must, can affect aroma production. The aim of this study was to examine the impact of several types of nitrogen sources added at different times during fermentation. Nitrogen was added as ammonium or a mixture of amino acids at the beginning of fermentation or at the start of the stationary phase. These conditions were tested with two Saccharomyces cerevisiae strains that have different nitrogen requirements. The additions systematically reduced the fermentation duration. The aroma production was impacted by both the timing of the addition and the composition of the nitrogen source. Propanol appeared to be a metabolic marker of the presence of assimilable nitrogen in the must. The production of ethyl esters was slightly higher after the addition of any type of nitrogen; the production of higher alcohols other than propanol was unchanged, and acetate esters were overproduced due to the overexpression of the genes ATF1 and ATF2 . Finally the parameter affecting the most the synthesis of beneficial aromas was the addition timing: The supply of organic nitrogen at the beginning of the stationary phase was more favorable for the synthesis of beneficial aromas. Highlights: Nitrogen content of the must impacts aroma production in alcoholic fermentation. The timing of addition and the source of nitrogen had an effect on aroma production. Acetate esters were the most impacted by nitrogen addition. After a nitrogen addition in stationary phase, ATF1 and ATF2 were overexpressed. The best results were obtained when adding organic nitrogen in stationary phase.